IL-4 Engagement of the Type I IL-4 Receptor Complex Enhances Mouse Eosinophil Migration to Eotaxin-1 In Vitro - Heller, Nicola M.; Gwinn, William M.; Donnelly, Raymond P.; Constant, Stephanie L.; Keegan, Achsah D. (PLOS ONE, 2012)
Background Previous work from our laboratory demonstrated that IL-4Rα expression on a myeloid cell type was responsible for enhancement of Th2-driven eosinophilic inflammation in a mouse model of allergic lung inflammation. Subsequently, we have shown that IL-4 signaling through type I IL-4 receptors on monocytes/macrophages strongly induced activation of the IRS-2 pathway and a subset of genes characteristic of alternatively activated macrophages. The direct effect(s) of IL-4 and IL-13 on mouse eosinophils are not clear. The goal of this study was determine the effect of IL-4 and IL-13 on mouse eosinophil function. Methods Standard Transwell chemotaxis assay was used to assay migration of mouse eosinophils and signal transduction was assessed by Western blotting. Results Here we determined that (i) mouse eosinophils express both type I and type II IL-4 receptors, (ii) in contrast to human eosinophils, mouse eosinophils do not chemotax to IL-4 or IL-13 although (iii) pre-treatment with IL-4 but not IL-13 enhanced migration to eotaxin-1. This IL-4-mediated enhancement was dependent on type I IL-4 receptor expression: γC-deficient eosinophils did not show enhancement of migratory capacity when pre-treated with IL-4. In addition, mouse eosinophils responded to IL-4 with the robust tyrosine phosphorylation of STAT6 and IRS-2, while IL-13-induced responses were considerably weaker. Conclusions The presence of IL-4 in combination with eotaxin-1 in the allergic inflammatory milieu could potentiate infiltration of eosinophils into the lungs. Therapies that block IL-4 and chemokine receptors on eosinophils might be more effective clinically in reducing eosinophilic lung inflammation.